A Possible Contribution of Altered Cathepsin B Expression to the Development of Skin Sclerosis and Vasculopathy in Systemic Sclerosis - Noda, Shinji; Asano, Yoshihide; Akamata, Kaname; Aozasa, Naohiko; Taniguchi, Takashi; Takahashi, Takehiro; Ichimura, Yohei; Toyama, Tetsuo; Sumida, Hayakazu; Yanaba, Koichi; Tada, Yayoi; Sugaya, Makoto; et al. (PloS one, 2012)
Cathepsin B (CTSB) is a proteolytic enzyme potentially modulating angiogenic processes and extracellular matrix remodeling. While matrix metalloproteinases are shown to be implicated in tissue fibrosis and vasculopathy associated with systemic sclerosis (SSc), the role of cathepsins in this disease has not been well studied. The aim of this study is to evaluate the roles of CTSB in SSc. Serum pro-CTSB levels were determined by enzyme-linked immunosorbent assay in 55 SSc patients and 19 normal controls. Since the deficiency of transcription factor Fli1 in endothelial cells is potentially associated with the development of SSc vasculopathy, cutaneous CTSB expression was evaluated by immunostaining in Fli1(+/-) and wild type mice as well as in SSc and control subjects. The effects of Fli1 gene silencing and transforming growth factor-β (TGF-β) on CTSB expression were determined by real-time PCR in human dermal microvascular endothelial cells (HDMECs) and dermal fibroblasts, respectively. Serum pro-CTSB levels were significantly higher in limited cutaneous SSc (lcSSc) and late-stage diffuse cutaneous SSc (dcSSc) patients than in healthy controls. In dcSSc, patients with increased serum pro-CTSB levels showed a significantly higher frequency of digital ulcers than those with normal levels. CTSB expression in dermal blood vessels was increased in Fli1(+/-) mice compared with wild type mice and in SSc patients compared with healthy controls. Consistently, Fli1 gene silencing increased CTSB expression in HDMECs. In cultured dermal fibroblasts from early dcSSc, CTSB expression was decreased compared with normal fibroblasts and significantly reversed by TGF-β1 antisense oligonucleotide. In conclusion, up-regulation of endothelial CTSB due to Fli1 deficiency may contribute to the development of SSc vasculopathy, especially digital ulcers, while reduced expression of CTSB in lesional dermal fibroblasts is likely to be associated with skin sclerosis in early dcSSc.